Visitors' willingness to pay for the enhanced conservation of the Mount Makiling Forest Reserve, Philippines - Torres, Keith Russel T.; Calderon, Margaret M. (2020)
The study aimed to estimate the value to visitors of the enhanced conservation of the Mount Makiling Forest Reserve (MMFR) using the contingent valuation method. Declared as the 33rd ASEAN Heritage Park (AHP) in 2013, the MMFR hosts unique flora and fauna which provides various ecosystem services. A hypothetical market for the enhanced conservation of MMFR was created where visitors could give to a fund for this purpose. Willingness to pay (WTP) was elicited using the single-bounded dichotomous choice format. A total of 102 respondents were interviewed over a four-week period, 63% of whom expressed WTP for the enhanced conservation of MMRF. Only bid level was found to significantly affect the respondents' WTP with the expected negative sign. A mean WTP of Php 110 on top of the current entrance fee was estimated through logit regression, while the non-parametic (Turnbull) WTP estimates were PhP 84.56 (lower bound) and Php 213.4 (upperbound). The results of this study may be used to capture visitors' WTP for the enhanced conservation of MMFR. If the visitors' mean WTP will be added to the current entrance fee, the potential revenues from 2009-2025 can total Php 35 million, and can be used to pertly finance the MMFR AHP Management Plan, which requires PhP 258.76 million for implementation.
Keywords: Mount Makiling Forest Reserve; Makiling Forest Reserve (Laguna); Willingness to pay; Forest conservation; Contingent valuation; Logit regression